Arteriopathy and microvascular impairment in sudden sensorineural hearing loss: Clues from two clinical cases. (June 2013) - Ciorba, Andrea; Faita, Antonio; Bianchini, Chiara; Aimoni, Claudia; Scanelli, Giovanni
Abstract The aetiopathogenetic mechanism of sudden sensorineural hearing loss (SSNHL) is still unclear. Microvascular impairment is one of the possible reported causes of SSNHL; nonetheless, few studies in the literature have investigated the association between SSHNL and vascular disease and a cause-effect relationship still has to be demonstrated. Two cases of SSNHL are presented and the possible role of vascular disorders in the pathogenesis of this disease is discussed.